EMPIRICAL INVESTIGATION ON RELATIONSHIP BETWEEN SAFETY MANAGEMENT PRACTICES AND SAFETY BEHAVIOR - Nur Aila Syafira Norzeri; Sallaudin Hassan; Zulhaimi Mohamad; Mohd. Farid Shamsudin; Nor Afiza Mohd Nor; Muhammad Asyraf Hasim (Marine Frontier, 2021)
Safety awareness programs have been actively conducted in order to inspire employee’s involvement and commitment toward safety. However, there are still many accidents and incidents reported involving workers at the workplace. Safety management practices improve working conditions, employee’s safety motivation and behavior, which in turn will reduce the accidents in the workplace. The main objective of this study is to investigate the relationship between safety management practices and safety behavior at work place. This is quantitative research whereby a survey questionnaire was use among 159 employees from services based company. Data has been analyzed using Statistical Package for Social Science (SPSS) version 21. This study discovered that safety management practices have a strong relationship with the safety behavior. Management commitment, safety training and worker’s involvement were the safety management practices that highly correlate the safety compliances and safety participation. This result provided valuable guidance for scholars and practitioners in identifying the method where they can improve safety at the workplace.